Giant splenic cyst: A case report and consolidated review of literature with radiographic features (Indian Journal of Case Reports, 2018)
The spleen is a relative stranger to the world of cysts and tumors, which when discovered, are often incidental findings in otherwise asymptomatic individuals. Splenic cysts are far more common than solid lesions and can include congenital, inflammatory, vascular, post-traumatic, neoplastic, and parasitic types. Parasitic cysts in the spleen are usually caused by the larval forms of Echinococcus, a cyclophyllid tapeworm. However rare, it is important to recognize the splenic presentation of this uncommon entity to prevent life-threatening complications like anaphylaxis induced by traumatic or spontaneous cyst rupture. We report here a case of a giant dumbbell-shaped splenic cyst. Hydatid disease of the spleen should be considered in the differential of every patient presenting with a cystic lesion of the spleen in the endemic areas until proven otherwise.